«Modern sovereigns». Alberto Aguilera’s Police Regulation for the Concierges of Madrid (1898) - Oviedo Silva, Daniel (Historia y Política, 2025)
In 1898, Alberto Aguilera, in his capacity as Civil Governor, passed the Police Regulation for the Concierges of Madrid. The main objective of its articles was to take advantage of the potential of these employees in surveillance tasks and turn them into auxiliaries of the authorities. This work draws on legislation as well as on newspaper and judicial sources to study the problematic articulation of police activity and the informal control tasks carried out by the concierges. The piece starts by looking at the context of the shortcomings of the Spanish public security structure in a context marked by rapid urbanisation as well as the centralisation and professionalisation of the state police apparatus. It goes on to analyse Aguilera’s project and pays special attention to the intersection of the public and private spheres, which is evidenced by the assignment of quasi-police tasks to private-sector workers. The article concludes with an examination of the concerns expressed by the neighbourhood about the measure —which was eventually repealed due to the opposition of owners, tenants and concierges— as an invasion of their privacy and rights. The study proves that the processes of modernising public security showed their structural weaknesses with the use of non-police auxiliaries and met with a certain degree of resistance. It also shows that, despite the failure of this initiative, similar laws were passed in the following decades and the use of concierges became ingrained in police culture and practice.